2012
DOI: 10.3201/eid1801.110671
|View full text |Cite
|
Sign up to set email alerts
|

Multistate Outbreak of MDR TB Identified by Genotype Cluster Investigation

Abstract: In 2008, diagnosis and investigation of 2 multidrug-resistant tuberculosis cases with matching genotypes led to identification of an outbreak among foreign-born persons who performed short-term seafood production work in Alaska during 2006. Tuberculosis control programs should consider the possibility of domestic transmission even among foreign-born patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…In several central Asian and eastern European countries, Ͼ30% of the newly diagnosed patients had MDR-TB, suggesting active transmission of primary drug-resistant strains (33). In several other countries, the primary transmission of MDR-/XDR-TB has been well documented (5,(34)(35)(36)(37). These reports showed that primary transmission played a major role in the epidemic of drug-resistant tuberculosis.…”
Section: Discussionmentioning
confidence: 78%
“…In several central Asian and eastern European countries, Ͼ30% of the newly diagnosed patients had MDR-TB, suggesting active transmission of primary drug-resistant strains (33). In several other countries, the primary transmission of MDR-/XDR-TB has been well documented (5,(34)(35)(36)(37). These reports showed that primary transmission played a major role in the epidemic of drug-resistant tuberculosis.…”
Section: Discussionmentioning
confidence: 78%
“…Eight clusters (57%) had an identifiable source case, seven (50%) were characterised by abuse of illicit drugs or alcohol, two (14%) included confirmed transmission to a child, 27 and one included transmission across state lines (table 3). 8 Overall, people with MDR tuberculosis attributed to transmission in the USA were more likely to be male (p<0·0001), have been born in the USA (p<0·0001), be of Hispanic ethnic origin (p<0·0001), abuse illicit drugs or alcohol (p<0·0001), and to have an M tuberculosis isolate of Euro-American lineage (p<0·0001) than were those who had disease not attributed to transmission in the USA (table 4). 75 (82%) of the 92 individuals who had an in-depth interview and health-record abstraction were born outside the USA.…”
Section: Resultsmentioning
confidence: 99%
“…7 Person-to-person transmission of MDR tuberculosis could be further fuelled by slow bacteriological conversion, delayed diagnosis and initiation of MDRspecific treatment, and treatment failure, as suggested by widespread outbreaks and secondary transmission of MDR tuberculosis within individual households and communities. [8][9][10] Migration of foreign-born individuals from areas with a high burden of MDR tuberculosis to those with a low burden could be an important factor. [11][12][13] A multiyear study of all cases of MDR tuberculosis reported in California, USA, showed that 92% were foreign-born individuals.…”
Section: Introductionmentioning
confidence: 99%
“…The methods were all, to some degree, based on geospatial concentration, and predictably did not identify outbreak “I” where the TB diagnoses occurred in three different states, even though M. tuberculosis transmission had occurred in a single workplace [15]. County-based LLR and SaTScan did not identify outbreak “D,” which was associated with the most common genotype in the United States, accounting for 1,077 (4.1%) of the 25,973 TB cases with a genotype result during 2008–2009.…”
Section: Discussionmentioning
confidence: 99%